Method for Increasing the Efficiency of Automatic Fire Extinguish System at Objects Of Power; MATEC Web of Conferences; Vol. 37 : Smart Grids 2015 - Dmitrienko M. A. Margarita Aleksandrovna (2015, 2015)
Title screen